Evaluation of the protective dose-dependent effect of metformin for induced osteoarthritis in rats - Ali Kadhim Challab Al-Buhadily,; Ali Ismail Abdulla Al-Gareeb, (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the potential protective effect of metformin against osteoarthritis development in rats. Method: The experimental study was conducted at the Iraqi Centre for Cancer Research and Medical Genetics, Mustansiriyah University, Baghdad, Iraq, from December 2021 to February 2022, and comprised male Sprague-Dawley mice who were divided into 5 equal groups: negative control group, osteoarthritis group subjected to monoiodoacetate induction, positive control group treated with celecoxib 30mg/kg, metformin 100mg/kg group, and metformin 200mg/kg group. Body mass index, inflammatory biomarkers, and serum C-terminal cross-linked telopeptide of type II collagen levels were noted for all the animals. Data was analysed using SPSS 24. Results: Of the 35 mice, 7(20%) were in each of the 5 groups. Compared to the osteoarthritis group, metformin-treated mice showed significantly reduced body mass index, inflammatory biomarker levels, and blood levels of C-terminal cross-linked telopeptide of type II collagen (p=0.05). Metformin 200mg/kg treatment had more beneficial effects than 100mg/kg dose on inflammatory biomarkers and serum C-terminal cross-linked telopeptide of type II collagen (p=0.05). Conclusions: A beneficial protective effect against the onset of osteoarthritis was produced by metformin in a dose-dependent way. Additionally, metformin could lessen cartilage damage as demonstrated by a decrease in the serum levels of C-terminal cross-linked telopeptide of type II collagen in the osteoarthritis group. Key Words: Collagen, Celecoxib, Osteoarthritis, Metformin, Cartilage